PHYSIOLOGICAL MECHANISMS OF EMOTIONS - Alikhanova Yulduz (International Journal of Literature and Language Studies, 2026)
Annotation: This article examines the physiological mechanisms of emotions and their role in human mental activity. The study analyzes the functioning of the central nervous system, the limbic system, the cerebral cortex, and the autonomic nervous system in the emergence and expression of emotional states. Particular attention is paid to the relationship between emotions and physiological processes, including changes in heart rate, respiration, hormonal activity, and neural responses. The findings indicate that emotions are complex psychophysiological phenomena that significantly influence behavior, cognition, and interpersonal relationships.